P12 Foundation realistic on-call simulation training (FROST): improving confidence at the transition from medical student to foundation doctor. (November 2018) - Feneley, Andrew; Badham, George; Gray, Victoria; Blake, Jessica; Featherstone, Barry
Abstract : Background: The transition between undergraduate and postgraduate medicine has been recognised as a target for simulation based education initiatives. We designed a programme to improve confidence of doctors starting their Foundation Year 1 (FY1) post in a trust of 3 district general hospitals. The programme was designed to allow the training of all 54 FY1 doctors within 6 days, to allow its integration into the mandatory shadowing period and minimise the necessity to release trainees after starting work. Summary of work: Ten scenarios were developed by the trust simulation team to expose the candidates to a number of tasks they may be expected to perform in an out-of-hours setting. Each candidate had a direct experience of one scenario. These scenarios were mapped to the Foundation Programme Curriculum. Scenarios were delivered in a simulation centre using a high fidelity manikin (SimMan 3G/Classic, Laerdal) with a member of faculty acting as a senior ward nurse. Scenarios were designed to be feasibly managed by the FY1 doctor alone with the help of the nurse and senior advice over the telephone, to improve confidence in working independently. Each scenario was followed by a structured debrief led by a trained facilitator. Debriefs covered technical and non-technical skills. In the pilot of this course, we were unable to access the FY1 doctors during their shadowing period and so the course was delivered over 6 days during the first 3 months of their post. Summary of results: All 54 FY1 doctors attended the course over the 6 days. Post course feedback indicated that the majority perceived that the course was realistic, relevant and useful. Participants were asked to indicate their perceived confidence in carrying out 'on-call' duties on a visual analogue scale before and after the course. Analysis revealed a statistically significant increase in median confidence, from 51% to 69%, with larger increases in earlier cohorts. Discussion and conclusions: This study shows that an SBE intervention of this type is useful to improve confidence at the transition from medical student to FY1 doctor. Furthermore, the intervention is appreciated by participants and can be delivered to large numbers in a short time period. Recommendations: The intervention will be delivered to the next intake of FY1 doctors within their shadowing period. Further work is required to ascertain whether the increase in confidence is retained in the long term and whether there are any improvements in patient outcome or safety. References: Cleland J, Patey R, Thomas I, et al . Supporting transitions in medical career pathways: The role of simulation-based education. Adv Simul (Lond) 2016;1:14. UK Foundation Programme Office. The Foundation Programme Curriculum 2016. Available at: http://www.foundationprogramme.nhs.uk/